Farewell Hong Kong - To, Erica (My University, 2024)
When we travel, we forge new friendships, explore new natural habitats, and begin to appreciate different ways of living. This five-minute video is a digital story of my dad who left Hong Kong to go to University of Oregon and study, so he can help his father (my grandfather) run a large business. But we all know that life is full of unexpected surprises. The people and places around us change our views and uncover values that resonate in our hearts. These self discoveries can be enough to make someone leave their home and live apart from their family. I am here because of my dad's decision to say farewell to Hong Kong, and I hope this video conveys my gratitude and appreciation.
Keywords: short documentaries